2019
DOI: 10.1016/j.stem.2019.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Precise Gene Editing Preserves Hematopoietic Stem Cell Function following Transient p53-Mediated DNA Damage Response

Abstract: Summary Precise gene editing in hematopoietic stem and progenitor cells (HSPCs) holds promise for treating genetic diseases. However, responses triggered by programmable nucleases in HSPCs are poorly characterized and may negatively impact HSPC engraftment and long-term repopulation capacity. Here, we induced either one or several DNA double-stranded breaks (DSBs) with optimized zinc-finger and CRISPR/Cas9 nucleases and monitored DNA damage response (DDR) foci induction, cell-cycle progression, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
343
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 264 publications
(381 citation statements)
references
References 58 publications
37
343
1
Order By: Relevance
“…We integrated CRISPRi technology with our previously described i 3 Neuron platform (Fernandopulle et al, 2018;Wang et al, 2017), which yields large quantities of highly homogeneous neurons, a prerequisite for robust population-based screens. We decided to use CRISPRi rather than CRISPRn, since CRISPRn-associated DNA damage is highly toxic to iPSCs and untransformed cells (Haapaniemi et al, 2018;Ihry et al, 2018;Schiroli et al, 2019). Furthermore, CRISPRi perturbs gene function by partial knockdown, rather than knockout, thereby enabling the investigation of the biology of essential genes.…”
Section: Introductionmentioning
confidence: 99%
“…We integrated CRISPRi technology with our previously described i 3 Neuron platform (Fernandopulle et al, 2018;Wang et al, 2017), which yields large quantities of highly homogeneous neurons, a prerequisite for robust population-based screens. We decided to use CRISPRi rather than CRISPRn, since CRISPRn-associated DNA damage is highly toxic to iPSCs and untransformed cells (Haapaniemi et al, 2018;Ihry et al, 2018;Schiroli et al, 2019). Furthermore, CRISPRi perturbs gene function by partial knockdown, rather than knockout, thereby enabling the investigation of the biology of essential genes.…”
Section: Introductionmentioning
confidence: 99%
“…In a cosubmitted manuscript, Ihry et al (2018) reported similar findings in another cell line. These results have since been independently reproduced by several groups using RPE-1 cells and other normal human cell types (Li et al, 2018;Cullot et al, 2019;preprint: Geisinger & Stearns, 2019;Schiroli et al, 2019;preprint: van den Berg et al, 2019). The significant attention that our work received was due to the relevance of our conclusions for genome editing in normal human cells and for the development of cell-based therapies.…”
mentioning
confidence: 78%
“…The major hurdle to exploit targeted gene editing in HSC is that procedures based on HDR suffer from limited efficiency in the most primitive progenitors, likely due to low expression and proficiency of the HDR machinery, cell quiescence, and limited uptake of repair template (Genovese et al, 2014). We recently investigated the transcriptional and functional impact of gene editing on HSPC and found that even a single DSB triggers a detectable transcriptional DDR with p53 pathway activation, p21 induction, and delayed cell proliferation (Schiroli et al, 2019). Yet, the extent of HDR-mediated DSB repair still decreases as we move from the most committed to the most primitive HSPC in culture, resulting in hematopoietic grafts of xenotransplant recipients comprising ≤ 20% HDR-edited cells in the long term and showing oligoclonal composition.…”
Section: Precision Genetic Engineering: Targeted Gene Editingmentioning
confidence: 99%
“…Because nuclease-mediated gene editing strictly depends on inducing DNA DSB, the concern was raised whether such breaks, albeit limited to few or even a single genomic site, trigger a DNA damage response (DDR) in the edited HSPC with the potential of inducing adverse effects on their key functional properties, such as long-term hematopoietic repopulation (Ciccia & Elledge, 2010;Milyavsky et al, 2010;Biechonski et al, 2018;Conti & Di Micco, 2018). We recently investigated the transcriptional and functional impact of gene editing on HSPC and found that even a single DSB triggers a detectable transcriptional DDR with p53 pathway activation, p21 induction, and delayed cell proliferation (Schiroli et al, 2019). The response was independent on the platform used for DSB induction and similar at different targeted loci.…”
Section: Precision Genetic Engineering: Targeted Gene Editingmentioning
confidence: 99%
See 1 more Smart Citation